Calculation of electric field distribution in the vicinity of power transmission lines with towers and unmanned aerial vehicles presence - Rezinkina, M. M.; Sokol, Yevgen I.; Gryb, O. G.; Bortnikov, A. V.; Lytvynenko, S. A. (Інститут електродинаміки НАН України, 2018)
The results of mathematical modeling of the electric field of overhead power transmission lines (TL) are presented taking into account presence of towers and unmanned aerial vehicles (UAVs) for various cases of the TL lines layout: vertical, horizontal and triangular. Numerical calculations of electric field (EF) were performed using finite integration technique and uniaxial perfectly matched layer. In this case the TL lines under the electrical potential were replaced by linear charges located on their axes. The obtained numerical results for the case of towers and UAV absence were compared with the analytical solutions, which showed coincidence of the EF strength moduli within the range of the assigned accuracy of the numerical calculations– 3%. The results of calculations are necessary to determine the flight height of UAVs, safe from the point of view of electromagnetic compatibility of the on-board electronics to influence of the TL EF and TL towers.

Представлено результати математичного моделювання електричного поля повітряних ліній електропередачі (ЛЕП) з урахуванням наявності опор і безпілотних літальних апаратів (БПЛА) для різних випадків розташування проводів ЛЕП: вертикального, горизонтального і трикутного. Чисельні розрахунки електричного поля (ЕП) виконувалися за допомогою методу кінцевого інтегрування і одновісно добре узгоджених шарів. При цьому струмопроводи, що знаходяться під потенціалом, замінялися лінійними зарядами, розташованими на їхніх осях. Виконано порівняння отриманих чисельних результатів для випадку відсутності опор і БПЛА з аналітичними рішеннями, яке показало збіг модулів напруженості ЕП у межах заданої точності чисельних розрахунків – 3%. Результати розрахунків необхідні для визначення висоти польоту безпілотних літальних апаратів, безпечної з точки зору електромагнітної сумісності бортової електроніки до дії ЕП ЛЕП та їхніх опор.
Розрахунок розподілу електричного поля в околиці ліній електропередачі з урахуванням наявності опор і безпілотних літальних апаратів
Keywords: electric field; mathematical modeling; overhead power transmission lines; electromagnetic compatibility; unmanned aerial vehicles; електричне поле; математичне моделювання; повітряні лінії електропередачі; електромагнітна сумісність; безпілотні літальні апарати